Exploring the landscape of focal amplifications in cancer using AmpliconArchitect - Viraj Deshpande (Nature Portfolio, 2019)
Focal amplifications are prevalent in many cancer genomes. Here, the authors present AmpliconArchitect (AA), a computational tool for reconstructing their architecture, and reveal an extrachromosomal origin for focal amplifications, including hybrid human-virus elements in HPV-mediated cancers.